Efficacy and safety of rituximab in myelin oligodendrocyte glycoprotein antibody-associated disorders compared with neuromyelitis optica spectrum disorder: a systematic review and meta-analysis. Issue 1 (25th October 2022) - Spagni, Gregorio; Sun, Bo; Monte, Gabriele; Sechi, Elia; Iorio, Raffaele; Evoli, Amelia; Damato, Valentina
Abstract : Background: Rituximab (RTX) efficacy in patients with myelin oligodendrocyte glycoprotein (MOG) antibody-associated disorders (MOGADs) is still poorly understood, though it appears to be lower than in aquaporin-4-IgG-positive neuromyelitis optica spectrum disorders (AQP4-IgG+NMOSDs). The aim of this systematic review and meta-analysis is to assess the efficacy and safety profile of RTX in patients with MOGAD and to compare RTX efficacy between MOGAD and AQP4-IgG+NMOSD. Methods: We searched original English-language articles published between 2012 and 2021 in MEDLINE, Cochrane, Central Register of Controlled Trials and clinicaltrials.gov, reporting data on RTX efficacy in patients with MOGAD. The main outcome measures were annualised relapse rate (ARR) and Expanded Disability Status Scale (EDSS) score mean differences (MDs) after RTX. The meta-analysis was performed with a random effects model. Covariates associated with the outcome measures were analysed with a linear meta-regression. Results: The systematic review included 315 patients (138 women, mean onset age 26.8 years) from 32 studies. Nineteen studies (282 patients) were included in the meta-analysis. After RTX, a significant decrease of ARR was found (MD: −0.92, 95% CI –1.24 to –0.60, p<0.001), markedly different from the AQP4-IgG+NMOSD (MD: −1.73 vs MOGAD −0.92, subgroup difference testing: Q=9.09, p=0.002). However, when controlling for the mean ARR pre-RTX, this difference was not significant. After RTX, the EDSS score decreased significantly (MD: −0.84, 95% CI −1.41 to –0.26, p=0.004). The frequency of RTX-related adverse events was 18.8% (36/192) and overall RTX-related mortality 0.5% (1/192). Conclusions: RTX showed effective in MOGAD, although to a lesser extent than in AQP4-IgG+NMOSD, while the safety profile warrants some caution in its prescription. Randomised-controlled trials are needed to confirm these findings and provide robust evidence to improve treatment strategies in patients with MOGAD. PROSPERO registration number: CRD42020175439.